Preferences, rent destruction and multilateral liberalisation: The building block effect of CUSFTA - Tobias Ketterer; Daniel M. Bernhofen; Chris Milner (Center for Economic Studies and ifo Institute (CESifo), 2012)
If a free trade agreement (FTA) is characterized by the exchange of market access with a large and competitive trading partner, the agreement can cause a leakage of protectionist benefits to domestic industry from lobbying against external tariff cuts. This rent destruction effect of an FTA can free policy makers to be more aggressive in multi-lateral tariff cuts. We argue that the Canadian-US free trade agreement (CUSFTA) provides an ideal policy experiment to link this mechanism to the data. Exploring the determinants of Canada's tariff cuts at the 8 digit HS product level, we find that CUSFTA acted as an additional driver of Canadian multilateral tariff reductions during the Uruguay Round.
Keywords: F13; F14; 330; preferences; rent destruction; multilateral liberalization; CUSFTA; Zollpräferenz; Freihandelszone; Interessenpolitik; Außenhandelsliberalisierung; Zolltarif; Rententheorie; Theorie; USA; Kanada